Network Pharmacology-Guided Evaluation of Apigenin in a Rat Model of Polycystic Ovary Syndrome with RT-PCR Validation of TNF-α Expression (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Polycystic ovarian syndrome (PCOS) is an endocrine disorder which is characterized by hormonal imbalance, insulin resistance, hirsutism, chronic inflammation of ovaries and metabolic disorders. Therapeutic approach for the disease is still incomplete. Apigenin, a naturally occurring flavonoid, exhibits anti-inflammatory property and antioxidant property has effect in treating PCOS but the molecular mechanism was not well understood. The current study network pharmacology with RT-PCR investigate the therapeutic mechanism of apigenin in PCOS induced rat model. Methodology Potential targets of apigenin and PCOS disease was identified using Pubchem and DisGenet respectively. Common genes identified using Interactive Venn and Cytoscape was used to create network among the disease and target with top 10 targets. In the top 10 target three genes were selected for RT PCR based on its cost and availability. Results & conclusion Network pharmacology identified TP53, ESR1, PPARG, PTGS2, HDAC1, NFE2L2, AR, CYP1A1, BRCA1, ESR2, and PGR as top targets. RT-PCR analysis of TNF-α demonstrated altered gene expression in the PCOS model and modulation following apigenin treatment, supporting the computational predictions and indicating restoration of ovarian function and inflammatory balance. These findings provide mechanistic evidence supporting the therapeutic potential of apigenin in PCOS.
Keywords: Apigenin; Polycystic ovarian syndrome; Network Pharmacology; Gene Expression; RT PCR; TNF – α